Efficacy and safety of tofacitinib as monotherapy in Japanese patients with active rheumatoid arthritis: a 12-week, randomized, phase 2 study. Issue 4 (July 2015) - Tanaka, Yoshiya; Takeuchi, Tsutomu; Yamanaka, Hisashi; Nakamura, Hiroyuki; Toyoizumi, Shigeyuki; Zwillich, Samuel
Abstract Objectives. To evaluate oral tofacitinib versus placebo for treatment of active rheumatoid arthritis in Japanese patients with inadequate response to disease-modifying antirheumatic drugs. Methods. In this double-blind, placebo-controlled, randomized, parallel-group, 12-week, phase 2 study (clinicaltrials.gov NCT00687193), 317 patients received tofacitinib: 1, 3, 5, 10, or 15 mg as monotherapy or placebo twice daily (BID). Primary endpoint: response rate by American College of Rheumatology (ACR) ≥ 20% improvement criteria (ACR20) at week 12. Results. ACR20 response rates: 37.7% (20/53), 67.9% (36/53), 73.1% (38/52), 84.9% (45/53), and 90.7% (49/54) with tofacitinib: 1, 3, 5, 10, and 15 mg BID, respectively, versus 15.4% (8/52) with placebo (p < 0.01; all doses). Dose-dependent ACR20 responses with tofacitinib versus placebo occurred from week 2 onward (p < 0.05). Changes from baseline in 28-joint disease activity score using erythrocyte sedimentation rate improved with tofacitinib versus placebo from week 4 (p < 0.01; all doses). Six tofacitinib patients experienced treatment-related serious adverse events (AEs). Most common treatment-emergent AEs: nasopharyngitis (10% vs 12%) and hyperlipidemia (5% vs 0%). Serum creatinine, hemoglobin, and total-, low-, and high-density lipoprotein-cholesterol levels increased with tofacitinib. Conclusions. Tofacitinib produced dose-dependent ACR20 responses and reduced disease activity. The safety profile was consistent with that reported from global monotherapy trials.